2021
DOI: 10.1364/oe.412692
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of molecular alignment and identification of multiple-orbital contribution by using polarized high harmonics from aligned N2 molecules

Abstract: With the parallel and perpendicular components of high harmonics generated by using aligned N2 molecules, we propose a method to retrieve the alignment distribution induced by the aligning laser based on the quantitative rescattering theory. And the intensity of pump laser and gas temperature can be precisely determined as well. We find that the intensity ratio between two harmonic components is very sensitive to the inclusion of multiple-orbital contribution in the theory. We thus suggest that it could be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
1
6
0
1
Order By: Relevance
“…However, the abnormal large value of H23 located between H17 and H19 curves in the experiment is still not reproduced by our simulation. Note that the peak value of the intensity ratio changes monotonically with the harmonic order for aligned N 2 molecules in Zhou et al [68], which has been successfully reproduced by our HHG theory [37]. Could the discrepancy be due to other effects that are not included in the QRS theory, like nuclear vibrations, hole dynamics, or electron-electron correlation?…”
Section: Comparison Of the Measured Intensity Ratios And The Simulate...supporting
confidence: 59%
See 1 more Smart Citation
“…However, the abnormal large value of H23 located between H17 and H19 curves in the experiment is still not reproduced by our simulation. Note that the peak value of the intensity ratio changes monotonically with the harmonic order for aligned N 2 molecules in Zhou et al [68], which has been successfully reproduced by our HHG theory [37]. Could the discrepancy be due to other effects that are not included in the QRS theory, like nuclear vibrations, hole dynamics, or electron-electron correlation?…”
Section: Comparison Of the Measured Intensity Ratios And The Simulate...supporting
confidence: 59%
“…Alternatively, it has been shown in Jin et al [36] that the minima in the HHG spectra of aligned CO 2 molecules are very sensitive to the degree of alignment, which could be used to retrieve the degree of alignment. Very recently, Guo et al [37] also suggested to use the polarization properties of the harmonics from aligned molecules to retrieve the alignment distribution. In the later method, both the intensity ratio and the relative phase between the parallel and the perpendicular components of the harmonics as a function of the pump-probe angle are needed.…”
Section: Introductionmentioning
confidence: 99%
“…激光诱导分子准直作为一个热门的研究课题,其最早由 Zon 提出 [1] .分子在 线偏振激光场中受到强场作用产生诱导偶极矩, 而后续激光场与偶极矩作用产生 扭力,使分子轴向激光场偏振方向偏转而产生准直效果.当激光场的持续时间远 小于分子的转动周期时,这一过程称为非绝热准直.在该过程中,激光脉冲对分 子转动波包的瞬态调制使分子的准直度迅速增加,而在激光消失后,分子各转动 能级的相干性并不会立即消失,转动波包会周期性演化一段时间,表现为分子准 直的周期性变化.目前,对分子准直度的表征方法主要有库仑爆炸法 [2] 、弱光偏 振法 [3] 和空间交叉聚焦散焦法 [4] .库仑爆炸法通过测量解离的分子碎片获得其空 间角分布,从而推出分子的准直度.该测量方案最直接,但仪器设备较大,实验 操作繁琐,存在较大误差,且库仑爆炸会破坏准直分子,无法开展基于分子准直 的后续实验测量.分子准直会引起介质的双折射现象,导致探测光偏振方向的变 化,测量垂直于初始探测光偏振方向的探测光分量强度,可提取分子准直度,即 弱光偏振法.该方法需要精确测量探测光的椭偏率,容易引入较大的实验误差, 影响测量结果的准确性. 空间交叉聚散焦测量法利用了分子准直后探测光空间强 度分布随介质折射率的变化,对探测光光斑中心区域的强度进行积分,得出分子 的准直度.相较于前两种方法,其实验操作和测量精度方面有了较大进步,但数 据处理较为复杂.研究人员发现,准直分子波包周期性演化使气体介质产生双折 射效应,会对探测光产生光谱调制 [5][6][7] .因此,可通过测量探测光光谱变化来表 征分子的准直度.相比于其它方法,光谱法能在短时间内通过多次重复测量减小 统计误差,且操作方便,但光谱无法直接得出准直度,需要进一步数据处理. 良好的分子准直在选择性控制同位素排列 [8] 、分子结构成像 [9] 及分子束纳米 光刻 [10] 、分子轨道重建 [11][12][13] 、高次谐波 [14][15][16][17][18] 等领域有重要作用.为了提高分子的 准直度,研究人员在尝试了提高泵浦脉冲能量、降温等手段外,还发展了多脉冲 泵浦法.Bisgarrd 研究小组 [19] 使用两束 1.4 ps 的长激光脉冲诱导碘苯分子的无场 准直, 发现当在第一束脉冲产生最大准直时刻附近加入第二束脉冲将明显提高分 子的准直度,并且在两束脉冲的强度比为 1:3 时分子准直度最佳.Ma 等人 [20]…”
unclassified
“…This phase can also be used to record the "core dynamics" [53] and it affects the polarization of the harmonics. [54] In general, 𝜙 𝑗 = 0 in the static tunnelling limit, while the non-adiabatic dynamics of electron rearrangement in the strong-field ionization would lead to a nonzero 𝜙 𝑗 . [4,53] To simulate high-harmonic spectra which can be directly compared with experimental data, one needs to consider the macroscopic response of HHG from a gas medium.…”
mentioning
confidence: 99%
“…Taking the even power of cos 𝜃 as the basis of expansion of the generalized Fourier expansion as in Ref. [54], we can expand 𝑁 1/2 (𝜃) as…”
mentioning
confidence: 99%